„Až sem přijde Adenauer, tak vy budete viset jako první!“, aneb ke specifikům trestného činu výtržnictví v socialistickém Československu - Milan Dobeš (Právněhistorické studie)
In this article, attention is paid to the examination of the criminal law provisions that regulated the punishment of riotous acts in socialist Czechoslovakia, with an emphasis on the application of the criminal offence of rioting by the District Court for Prague 1. In addition to the common cases of rioting, cases with political overtones and the possibility of abusing the crime of rioting against people who were inconvenient to the regime (dissidents) are also included. The first chapters generally address the legal regulation of riotous offences since the fifties. The fifties are also supplemented with contemporary cases. The article’s core consists of subsequent chapters focusing on the regulation of rioting according to § 202, codified in the Criminal Code of 1961. For a better understanding of the legal regulation at that time, there are cases from the then-practice, which were handled by the District Court for Prague 1. The following part pays attention to riotous acts that accompanied the opposition to the regime at that time, and the last subchapter points out the misuse of the crime of rioting and the distortion of its factual essence by the then-state against its opponents.